Exploring family caregiver challenges in caring for patients with COVID-19 in intensive care units - Najafi Ghezeljeh, Tahereh; Rezaei, Masoud; Keyvanloo Shahrestanaki, Sahar; Sheikh Milani, Arezoo (Frontiers in Public Health, 2023)
ABSTRACT Background: Families with a member who is suffering from acute and fatal diseases such as COVID-19 and hospitalized in intensive care units (ICU), are facing many physical and mental health stresses. Identifying the challenges of family members and helping them in life-threatening situations can help in better treatment and care for family members. Aim: The current study was conducted to explain the experiences of family caregivers with a COVID-19 patient in the ICU. Method: This descriptive qualitative study was conducted from January 2021 to February 2022, based on the experiences of 12 family caregivers of patients with COVID-19 hospitalized in the ICU. Data collection was done by purposeful sampling with semi-structured interviews. MAXQDA10 software was used for data management, and conventional content analysis was used for qualitative data analysis. Results: From the interviews with caregivers, three categories and eighty subcategories obtained based on their experiences of having a family member in the ICU. the first category was Hardship of Care Trajectory that extracted from immersion in the unknowns, lack of caring facilities, negligence in caring, ignoring the family by health care providers, self-ignorance, perceived stigma; the second category was Pre-loss Mourning that extracted from emotional and psychological turmoil, witness the exhaustion of loved ones, separation suffering, fearing of loss, anticipatory grief, blame the disease causative agents, perceived helplessness and despair and the third category of this study was Contributing Factors Resolving the Family Health Crisis that extracted from the individual role of the family caregiver in health engagement, the role of professionals into health engagement and the role of interpersonal factors in health engagement. Conclusion: This research showed that families can play an important role in resolving the health problems of patients in life-threatening situations such as the COVID-19 pandemics. Moreover, family-based care should be more attended by health care providers. They should trust the ability of families to solve health crises and be alert about the needs of patient’s family members and the patient's needs. KEYWORDS: COVID-19, Intensive Care Unit, Family, Family Caregivers, Qualitative Study